ANALISIS PROSEDUR AKUNTANSI PENERIMAAN PAJAK DAERAH PADA PPK-SKPD DINAS PENGELOLAAN KEUANGAN DAERAH KOTA TANGERANG - Irma Wati (Media Riset Akuntansi, Auditing & Informasi, 2014)
Each SKPD has rights and duties in collecting and calculating the local tax revenues in accordance with the provisions of the applicable legislation. The purpose of do internship, was to determine whether the accounting procedures of local tax revenue in the PPK-SKPD at DPKD is in conformity with the provisions of the applicable legislation. To obtain the necessary data, a writer collecting data by interviews, observation, and documentation. The results obtained in the implementation of internship in DPKD is the accounting procedures of local tax revenue in the PPK-SKPD are in accordance with Regulation 36 of 2012 Tangerang Mayor Annexes III and SE BAKD No. 900/316. The application of theaccounting procedures of local tax revenue in the PPK-SKPD has a major influence on the accountability of the financial statements. But in to result financial reports accountable, DPKD should doing an adequate evaluation of the application system are implemented and resources used.